Uncovering student misconceptions: A watson's framework analysis of roman numerals problems - Aida Sari, Fitri; Nurdiyah Kurniati (LINEAR: Journal of Mathematics Education, 2025)
This study analyzes the errors made by second-semester students of the Elementary School Teacher Education Study Program in solving Roman numeral problems. This study uses a descriptive qualitative approach with 35 students as subjects selected through purposive sampling techniques. The research instrument used six questions to identify errors based on Watson's categories: inappropriate data, inappropriate procedures, omitted data, omitted conclusions, response level conflicts, undirected manipulation, skills hierarchy problem, and other errors (not providing answers). The analyzed data was reduced, presented, and concluded. The study's results indicate that other errors (specifically about students who did not provide answers) were the most dominant (40.41%), with details of the errors that occurred in numbers 2, 3, 4, 5, and 6, respectively, 5.48%, 4.11%, 3.42%, 13.70%, and 13.70%. Other types of errors were response-level conflicts, inappropriate procedures, undirected manipulation, omitted conclusions, and inappropriate data. The implications of this study emphasize the importance of conceptually understanding-based learning in teaching Roman numerals.